The Creation of the City of Baghdad: Striking a Balance between Religion and the Quest for Power - Spahic, Omer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Creation of the City of Baghdad: Striking a Balance between Religion and the Quest for Power